1998
DOI: 10.1098/rstb.1998.0268
|View full text |Cite
|
Sign up to set email alerts
|

Disease conditions and subclinical infections of the platypus (Ornithorhynchus anatinus)

Abstract: Before the arrival of European settlers in Australia, the platypus, Ornithorhynchus anatinus , probably suffered from little disease. Among other things, European settlement has involved substantial environmental perturbation, introduction of large predators, introduction of motor vehicles and translocation of potential pathogens. As a result, platypuses are now killed by motor vehicles, dogs, foxes and discarded plastic litter. Information programmes targeting appropriate segments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 17 publications
2
39
1
Order By: Relevance
“…The disease was first detected in platypuses from the Elizabeth River in Tasmania's northern midlands in 1982 (Munday and Peel, 1983). The fungal pathogen responsible was identified as Mucor amphibiorum (Obendorf et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease was first detected in platypuses from the Elizabeth River in Tasmania's northern midlands in 1982 (Munday and Peel, 1983). The fungal pathogen responsible was identified as Mucor amphibiorum (Obendorf et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…All animals were individually identified on the first capture with a passive integrated transponder (PIT) tag (Trovan, Hessle, East Yorkshire, UK or Allflex, Capalaba, Queensland, Australia) inserted subcutaneously between the scapulae. Visual health assessments were made by physical examination of each captured individual to determine the presence of ulcers, granulomas, wounds, or other abnormalities (Munday and Peel, 1983;Connolly et al, 1998). Individuals were considered to be clinically healthy when no external injuries or lesions were observed and there was no evidence of disease or emaciation.…”
Section: Live Trapping Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Gust and Handasyde (1995) and Bethge et al (2003) found a mean foraging durations of ~10 hr/day and 11.5 hr/day respectively. During foraging trips, platypuses have been observed to move distances of a few hundred metres to several kilometres along rivers and/or streams and have been known to move over land to avoid obstructions such as waterfalls, culverts or meanders in rivers (Serena 1994;Gardner and Serena 1995;Gust and Handasyde 1995;Munday et al 1998;Mooney and Spencer 1999). In this study, we investigate the novel use of instream microchip readers as a remote, long-term and relatively non-labour intensive method of monitoring microchipped wild platypuses as they move along waterways during foraging.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, 536 a study of native Australian mammals identified Ixodes australiensis 537 as the vector for Trypanosoma copemani (Austen et al, 2011). PB70 PB09 PB72 PB74 PB76 PB81 PB82 PB85 PB90 PTL57 PB52 PB89 PB78 PB94 PB77 PB88 PB80 PB75 (Anderson and Ayala, 1968), and a midge 546 (Corethrella wirthi) one from a treefrog (Hyla cinerea) (Johnson 547 et al, 1993) (reviewed by (Hamilton et al, 2004) as already suggested (Munday et al, 1998); thus, until further 551 studies are conducted, this debated theory cannot be refuted.…”
mentioning
confidence: 99%